Evaluating performance with implementation of virtualised data in the cloud using metaheuristic approach. Issue 3 (2017) - Mishra, Jyoti Prakash; Mishra, Sambit Kumar
Cloud computing provides access to the cloud resources such as storage and business applications from anywhere only by connecting to the internet. However, there are several issues that come along with the benefits of cloud computing. Cloud computing is not only been reshaped the field of distributed systems but also extend businesses potential. Virtual machine enables the abstraction of an operating system and application running on it from the hardware. Virtualisation provides the basic features such as flexibility, cost effectiveness, scalability. The main goal of virtualisation is managing the workloads by transforming the traditional computing units to make it more scalable. It can be applied to a wide range of system layers, including operating system level and hardware level virtualisation. In this article, it is aimed to evaluate performance of virtualised data and to identify the security issues of virtualisation in the cloud computing environments.